1990
DOI: 10.2307/249313
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Learning Style in End-User Training

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Management Information Systems Research Center, University of Minnesota is collaborating with JSTOR to digitize, preserve and extend access to MIS Quarterly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(180 citation statements)
references
References 41 publications
1
142
0
1
Order By: Relevance
“…A number of studies have demonstrated that personality preferences and/or learning styles have an effect on student use of CAI (Bostrom et al, 1990;Ames, 2003;Cook, 2005b;Manochehr, 2006). We previously reported that ''Sensors'' used both the ''Forum'' and ''Flash'' CAI more extensively than ''Intuitives' ' (McNulty et al, 2006), which was validated in this multi-year investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that personality preferences and/or learning styles have an effect on student use of CAI (Bostrom et al, 1990;Ames, 2003;Cook, 2005b;Manochehr, 2006). We previously reported that ''Sensors'' used both the ''Forum'' and ''Flash'' CAI more extensively than ''Intuitives' ' (McNulty et al, 2006), which was validated in this multi-year investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable is learning effectiveness. When assessing elearning effectiveness, we need to consider not only the actual effectiveness of the learning content, but also the perceived effectiveness of the e-learning system [29] because the degree of satisfaction with the learning achievement in on-line courses is a critical factor in determining learning effectiveness [30]. In addition, Lowerison, Sclater, Schmid, and Abrami [2] suggested that positive learning experiences include the users' feeling that they have effectively interacted with the instructor and other students, and that the users feel in control of their own learning by means of their active participation.…”
Section: Learning Effectivenessmentioning
confidence: 99%
“…Incorporating with the theories in cognitive psychology, educational psychology, information systems, and computer science, Bostrom et al [2] proposed an end-user training research framework which consists of five variables-target system, training methods, individual differences, mental model, and training outcomes. Their findings suggested that different training methods should be used for different learners.…”
Section: A End-user Trainingmentioning
confidence: 99%
“…[2], Piccoli et al [8], and Sun et al [13], we developed a research model (Fig. 1) in order to examine the factors influencing the success of the use of Facebook Groups as an e-learning environment to support a face-to-face course.…”
Section: A Research Modelmentioning
confidence: 99%
See 1 more Smart Citation